An Analysis of Feasibility Study of Gimbo Honey Business Development in Kota Bengkulu - Erza Dwi Sartika; Sulisti Afriani; Rina Trisnayanti (Penerbit Jurnal Indonesia, 2021)
The purpose of this study is to determine the feasibility of developing Gimbo honey business in Bengkulu city. The analysis method used is a feasibility study analysis from the financial aspect which includes Net Present Value (NPV), Internal Rate Of Return (IRR), Gross Benefit Cost Ratio (Groos B / C), and Payback Period (PP). The results showed the value of Net Presen Value (NPV), indicating a positive or large number of 0 (zero), namely Rp. 0.33, -, meaning that the expansion of Gimbo Honey Business in Bengkulu City can be said to be feasible to be developed. The internal rate of return (IRR) is known to be 13.22% greater than the percentage of the cost of capital (credit interest), which is 12%, which means that the expansion of the business is feasible for development. This shows that if the funds for investment are saved or deposited to a bank with an interest rate of 12% or better, it is developed because it will generate an interest rate of 13.22%. Gross B / C is greater than 1 (4.97> 1). and Payback Period (PP) of 2 years 11 months shows that you can get back the invested funds within 7.5 months, meaning that the business development of Gimbo Honey Business in Bengkulu City can be continued. This shows that the level of income is greater than the total cost so that an investment of IDR 262,935,000 can be continued.